Justice system integration: on the threshold of a new era. - Harris, Kelly J. (Corrections Today, 1999)
Part of a special section on the use of technology in the corrections profession. A federal law that comes into effect in 1999 provides necessary funding for justice information system integration. The Crime Identification Technology Act of 1998 provides $250 million annually for the next five years for state grants to promote the integration of identification technology and justice system information. According to Senator Mike DeWine, R-Ohio, the new law will permit greater sharing of information and communication between all components of criminal justice. The Act will also provide grants for states so they can participate in programs such as the Integrated Automated Fingerprint Identification System, the National Crime Information Center 2000, and the National Incident-Based Reporting System Project. Members of the justice system have become more comfortable with computers and now acknowledge the functionality that effective information systems can offer.